1989
DOI: 10.1182/blood.v74.2.645.bloodjournal742645
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of erythropoietin-producing cells in kidneys of mice by in situ hybridization: correlation with hematocrit, renal erythropoietin mRNA, and serum erythropoietin concentration

Abstract: In situ hybridization was used to quantitate the cells that produce erythropoietin (EP) in the renal cortices of mice with varying severities of acute anemia and of mice recovering from severe, acute anemia. The number of EP-producing cells in the renal cortex increased in an exponential manner as hematocrit was decreased. Individual EP- producing cells had very similar densities of silver grains in autoradiograms regardless of whether they were from normal mice or from slightly, moderately or severely anemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…9 In addition, it is expected that reduced blood O2 carrying capacity (anemia) or ambient O2 concentration (hypoxia) stimulates increased erythropoietin RNA synthesis. [28][29][30][31] The upregulation of erythropoietin (Epo) and VEGF by hypoxia has been demonstrated. 32 Epo induces physiological activities such as cell proliferation, migration, and angiogenesis as VEGF does.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, it is expected that reduced blood O2 carrying capacity (anemia) or ambient O2 concentration (hypoxia) stimulates increased erythropoietin RNA synthesis. [28][29][30][31] The upregulation of erythropoietin (Epo) and VEGF by hypoxia has been demonstrated. 32 Epo induces physiological activities such as cell proliferation, migration, and angiogenesis as VEGF does.…”
Section: Discussionmentioning
confidence: 99%
“…Production by the liver, however, may not be an 'all or nothing' phenomenon. Koury et al (1991) have recently shown that hepatocytes surrounding the central veins are the major sites of expression of the mRNA for the human Epo in the liver of a transgenic anaemic mouse. They were, however, unable to clearly define if non-transgenic adult mice produced Epo in this fashion or not.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, the mechanisms of the renal and the hepatic Epo expression differ. (i) Renal cells respond in an all-or-nothing fashion to hypoxia (Koury et al 1989), whereas hepatoma cells respond in a graded way. (ii) The hypoxia-response elements (HREs) in control of the Epo gene are located upstream in the kidney (between 9.5 and 14 kb 5 to Epo) but downstream in the liver (within 0.7 kb 3 to Epo) according to studies in transgenic mice (Kochling et al 1998).…”
Section: Molecular Mechanism Of the Hypoxia-induced Epo Expressionmentioning
confidence: 99%